2010
DOI: 10.1289/ehp.1002720
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls, Lead, and Mercury Are Associated with Liver Disease in American Adults: NHANES 2003–2004

Abstract: BackgroundHigh-level occupational exposures to some industrial chemicals have been associated with liver diseases, including nonalcoholic fatty liver disease (NAFLD). However, the potential role of low-level environmental pollution on liver disease in the general population has not been evaluated.ObjectiveWe determined whether environmental pollutants are associated with an elevation in serum alanine aminotransferase (ALT) activity and suspected NAFLD in U.S. adults.MethodsThis cross-sectional cohort study eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
232
3
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(248 citation statements)
references
References 37 publications
6
232
3
7
Order By: Relevance
“…Increased risk for sleep apnea stems from the impact of elevated blood pressure and constraints on the pulmonary system from increased BMI (85,86). NAFLD has been associated with exposures to chemicals such as organic compounds or metals in cross-sectional analysis of population data (87,88) and among workers with or without metabolic disease (89). The association of sleep apnea with NAFLD is gaining support (90) and the association of obesity with NAFLD is becoming a greater concern given the obesity epidemic (91).…”
Section: Example 14: Obesity Sleep Apnea and Non-alcoholic Fatty Lmentioning
confidence: 99%
“…Increased risk for sleep apnea stems from the impact of elevated blood pressure and constraints on the pulmonary system from increased BMI (85,86). NAFLD has been associated with exposures to chemicals such as organic compounds or metals in cross-sectional analysis of population data (87,88) and among workers with or without metabolic disease (89). The association of sleep apnea with NAFLD is gaining support (90) and the association of obesity with NAFLD is becoming a greater concern given the obesity epidemic (91).…”
Section: Example 14: Obesity Sleep Apnea and Non-alcoholic Fatty Lmentioning
confidence: 99%
“…Several factors, including genetics, diet, lifestyle, and age, have been implicated in the development of NAFLD and associated metabolic disorders including diabetes, dyslipidemia, and cardiovascular disease (Pitsavos et al, 2006;. Recent studies also suggest exposure to environmental contaminants including persistent organic pollutants and organochlorines contributes to metabolic disease development (Cave et al, 2010;Lee et al, 2006Lee et al, , 2007Taylor et al, 2013). For example,2,3,7,, the prototypical aryl hydrocarbon receptor (AhR) ligand, has been shown to contribute to the progression of NAFLD spectrum from simple, reversible steatosis, to steatohepatitis and early signs of fibrosis in mice (Kopec et al, 2013;Nault et al, 2015a;Pierre et al, 2014).…”
mentioning
confidence: 99%
“…The authors concluded that these results suggested that the organic form of mercury was associated with liver disease (Cave et al, 2010). However, PCB and lead exposure were also associated with an increased ALT activity, and the influence of the co-exposure to these other pollutants was not evaluated by the authors.…”
Section: Miscellaneous Endpointsmentioning
confidence: 95%